Subgingival chlorhexidine irrigation for scaling and root planing adjunctive therapy in chronic periodontitis: a systematic review (Medical Journal of Indonesia, 2022)
BACKGROUND Scaling and root planing (SRP) is a conventional treatment for chronic periodontitis; however, it has limitations in treating deep pockets. To enhance its efficacy, chlorhexidine (CHX) is proposed as adjunctive therapy with SRP due to its broad antimicrobial spectrum, low systemic toxic activity in humans, absence of oral microorganism resistance, and lack of teratogenic effects. This study aimed to know the efficacy of the adjunctive therapy of CHX. METHODS A literature search was conducted using various databases including PubMed, LIVIVO, EBSCOhost, and Google Scholar, following the Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines within the last 10 years (2011–2021). Clinical parameters such as plaque index (PI), gingival index (GI), bleeding on probing (BOP), pocket depth (PD), and clinical attachment level (CAL) were recorded. The risk of bias in the selected studies was assessed using Cochrane Collaboration’s Handbook version 5.2.0. RESULTS Of 368 studies, 10 met the inclusion criteria, with 8 of them having a higher quality. Higher reduction of PI, GI, BI, PD, and CAL were observed in SRP with CHX irrigation compared with SRP alone. CONCLUSIONS Overall, adding CHX to SRP appeared to have additional clinical benefits compared with SRP alone in the treatment of chronic periodontitis.